2016
DOI: 10.1080/10810730.2015.1095820
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of Mass-Mediated Health Campaigns Through Meta-Analysis

Abstract: A meta-analytic review was undertaken to examine the effects of mass communication campaigns on changes in behavior, knowledge, and self-efficacy in the general public. A review of the academic literature was undertaken and identified 1,638 articles from 1966 through 2012. Using strict inclusion criteria, we included 63 studies for coding and analyses. Results from these efforts indicated that campaigns produced positive effects in behavior change (r = .05, k = 61) and knowledge (r = .10, k = 26) but failed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 89 publications
3
67
0
1
Order By: Relevance
“…Quality of life and savings in disability-adjusted life years resulting from delaying the onset of type 2 DM should be quantified and qualified, especially among high-risk populations like Hispanics/Latinos. Also, the evaluation of type 2 DM risk prevention in multilevel community studies to prevent childhood obesity ( 331 , 332 ), coupled with mass media campaigns to increase awareness of type 2 DM prevention ( 336 , 439 ), and other risk factors for diabetes, is warranted.…”
Section: Preventing Type 2 Dm In Hispanics/latinos—a Holistic Framewomentioning
confidence: 99%
“…Quality of life and savings in disability-adjusted life years resulting from delaying the onset of type 2 DM should be quantified and qualified, especially among high-risk populations like Hispanics/Latinos. Also, the evaluation of type 2 DM risk prevention in multilevel community studies to prevent childhood obesity ( 331 , 332 ), coupled with mass media campaigns to increase awareness of type 2 DM prevention ( 336 , 439 ), and other risk factors for diabetes, is warranted.…”
Section: Preventing Type 2 Dm In Hispanics/latinos—a Holistic Framewomentioning
confidence: 99%
“…Soft outcomes (knowledge, attitude, behaviour or preferences) were assessed in two campaigns (Brazil and Iran) but only immediately after exposure to the campaign. The duration of mass media effects, that is, the persistence of the positive effects of mass media on knowledge, attitude, behaviour or preferences over time, is considered an important element in assessing the effectiveness of mass media interventions 27 28 44. This was not reported by any of the campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews have shown the effectiveness of mass media campaigns targeted at reducing unhealthy habits or promoting healthy behaviours such as breast feeding or family planning, among others 21–27. However, significant changes in behaviour can be achieved only when campaigns are well designed and carried out at sufficient scale and intensity 21 28–36…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impact of the media on cancer awareness has been well documented. Several studies reported increased screening for cancer and improved awareness in the USA and Australia after mass media campaigns, involving newspapers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impact of the media on cancer awareness has been well documented. Several studies reported increased screening for cancer and improved awareness in the USA and Australia after mass media campaigns, involving newspapers [25,26].Knowing that newspapers represent an important source of health information after the internet [27], it is of immense value to investigate how newspapers report on healthcare apps. To date, there is no published research that investigates the newspaper reporting of healthcare apps, therefore, the aim of the present study is to explore what the general public have been told about healthcare apps within published newspaper articles in the US and UK over a ten-year period (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and to analyse the content of the articles.…”
mentioning
confidence: 99%